Sporotrichosis: hyperendemic by zoonotic transmission, with atypical presentations, hypersensitivity reactions and greater severity - Regina Casz Schechtman; Eduardo Mastrangelo Marinho Falcão; Marciela Carard; Maria Salomé Cajas García; Diana Stohmann Mercado; Roderick James Hay (Sociedade Brasileira de Dermatologia, 2022)
Abstract In recent decades, an alarming increase in the number of sporotrichosis cases has been reported in southern and southeastern Brazil, especially in the state of Rio de Janeiro, has been considered a long-term hyperendemic condition associated with feline transmission. According to phenotypic classifications, the Sporothrix species recovered from cats were classified as S. brasiliensis in 96.5% of the studied cases. This finding has also been demonstrated in humans, which confirms the zoonotic transmission associated with this predominant species in Brazil. The zoonotic transmission of the fungus and its important virulence in the context of the hyperendemic situation in Rio de Janeiro have changed the approach to the disease, which in its classic form was restricted to certain professional groups and very specific regions in the Brazilian territory, into a public health challenge of scientific interest. Its atypical manifestations and hypersensitivity reactions are increasingly frequent, constituting a new sporotrichosis aspect, which deserves attention from the medical community, as well as from other health professionals.